1995
DOI: 10.1002/jqs.3390100106
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene—pleistocene boundary in the Kleszczów Graben at Belchatów, central Poland

Abstract: The Pliocene-Pleistocene boundary, defined using pollen analysis, has been recorded in sections at the Betchat6w outcrop, Kleszczow Graben, central Poland. The boundary is located at the top of the green clay subunit of the Tertiary Clayey-sandy unit. A pollen flora of Reuverian C type, dominated by pine, 10-20% of 'Reuverian elements' and scarce thermophilous Tertiary trees, was found directly below this subunit. Cold stage floras of Praetiglian type were, in turn, recorded in the tekilisko Formation, lying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…A palynological analysis of organic beds has revealed cool Pleistocene floras. Krzyszkowski & Szuchnik (1995) evidenced that the heavy-mineral spectrum was nearly the same as in Neogene deposits, only some increase of garnet frequency and sand-grain roundness was noted. They concluded that there was no hiatus between the Neogene Clayey-sandy Unauthenticated Download Date | 5/11/18 1:14 PM Complex and the Pleistocene Łękińsko Series.…”
Section: łęKińsko Seriesmentioning
confidence: 80%
See 4 more Smart Citations
“…A palynological analysis of organic beds has revealed cool Pleistocene floras. Krzyszkowski & Szuchnik (1995) evidenced that the heavy-mineral spectrum was nearly the same as in Neogene deposits, only some increase of garnet frequency and sand-grain roundness was noted. They concluded that there was no hiatus between the Neogene Clayey-sandy Unauthenticated Download Date | 5/11/18 1:14 PM Complex and the Pleistocene Łękińsko Series.…”
Section: łęKińsko Seriesmentioning
confidence: 80%
“…These are so-called 'brown sands' which underlie Quaternary deposits at Bełchatów. Krzyszkowski & Szuchnik (1995) studied the organic beds in the top part of the Clayey-sandy Complex and noted that it was difficult to correlate the pollen assemblage from these beds with Pliocene spectra of other Polish sites. Those authors found some similarities to Late Pliocene (cool phase C of Reuverian, sensu Zagwijn) in northwest Europe.…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations